Engineering CXCL12 Biomimetic Decoy‐Integrated Versatile Immunosuppressive Nanoparticle for Ischemic Stroke Therapy with Management of Overactivated Brain Immune Microenvironment. Issue 1 (10th November 2021) - Shi, Jinjin; Yang, Yue; Yin, Na; Liu, Changhua; Zhao, Yuzhen; Cheng, Hui; Zhou, Tonghai; Zhang, Zhenzhong; Zhang, Kaixiang
Abstract: Following ischemic stroke, brain‐resident activated microglia and peripherally infiltrated inflammatory cells create a complicated and overactivated brain immune microenvironment, which causes neuron death and dramatically hinders neurological functional recovery. Herein, an engineering CXCL12 biomimetic decoy‐integrated versatile immunosuppressive nanoparticle (VIN) for management of the overactivated brain immune microenvironment is reported. The shell of VIN (membrane of CXCR4 overexpressed mesenchymal stem cells), can not only improve the homing of nanoparticles to the cerebral ischemic lesions, but also efficiently adsorb and neutralize CXCL12 to cut off infiltration of peripheral‐neutrophils and mononuclear macrophages. The loaded A151 (cGAS inhibitor, telomerase repeat sequences) can inhibit cGAS‐STING pathway in microglia, leading to microglia polarization toward an anti‐inflammatory M2‐like phenotype. Interestingly, A151 can be efficiently loaded onto the polydopamine nanospheres (PDA, the core of VIN) through the bridge of Zn 2+ . In the inflammatory site, PDA is oxidized by reactive oxygen species (ROS), with the disappearance of Zn 2+ complexation effect, and then A151 realizes a controlled release. In a model of rat ischemic stroke, VIN integrates inflammation tropism, peripherally inflammatory cells filtrate, brain‐resident activated microglia polarization, as well as, ROS scavenging, exerting outstanding therapeutic effects on ameliorating the mortality, reducing the infarct volume, and protecting neurogenic functions of neurons. Abstract : An engineering CXCL12 biomimetic decoy‐integrated versatile immunosuppressive nanoparticle (VIN) is reported. VIN integrates inflammation tropism, peripherally inflammatory cells filtrate, brain‐resident activated microglia polarization, as well as, ROS scavenging. As a result, the VIN can promote outstanding therapeutic effects on ameliorating the mortality, reducing the infarct volume, and protecting neurons post‐stroke.